Statistical Models of Shape - Yanhong, Shi (Springer, 2017)
The retinal pigment epithelium (RPE) plays a key role in supporting pho-toreceptor survival and function, and RPE loss and dysfunction in age-related macu-lar degeneration (AMD) leads to photoreceptor death. AMD is one of the leading causes of blindness, yet there is neither a cure nor a way to prevent it. In this chapter, we discuss recent progress in the study of AMD, summarize what is known about RPE development, and review recent progress in deriving RPE from human embry-onic stem cells (hESC). The RPE is derived from the optic vesicle, which in turn is derived from the eye field of the anterior neural plate. Multiple extracellular signal-ing factors and transcriptional regulators have been identified that are crucial to RPE development. Knowledge of these events is guiding efforts to understand how hESC differentiate into RPE cells that might be used therapeutically for AMD. RPE derive from hESC are remarkably similar to fetal RPE with respect to gene expression and cellular function. Future research on these cells will lead to a better understanding of RPE development and the advancement of cellular therapy for AMD.